The Relations Between Electrocardiographic QRS Duration and Echocardiographic Left Ventricular Dimensions - Hossain, Md. Emran; Islam, Roksana; Hoda, Durul; Jahangir, Nuruddin; Chowdhury, Mohammad Moinuddin; Mehedi, Hamidullah (Cardiology and Cardiovascular Medicine, 2021)
Background: The QRS duration denotes the time for ventricular depolarization. Normally, the QRS duration is 0.06 to 0.10 seconds. The measurement of left ventricular dimensions and the changes of left ventricular function are important to assess cardiac as well as the cardiovascular conditions of patients. We have very limited research-based information regarding the relation between electrocardiographic QRS duration and echocardiographic left ventricular measurements in individuals without heart failure (HF) or myocardial infarction (MI). Aim of the study: The aim of this study was to assess the correlations between electrocardiographic QRS duration and echocardiographic left ventricular measurements in individuals without heart failure (HF) or myocardial infarction (MI). Methods: This cross-sectional study was conducted in the Department of Cardiology, University Cardiac Centre, Bangabandhu Sheikh Mujib Medical University, Dhaka over a period of 2 years from July 2008 to June 2010. In total 92 apparently healthy people without heart failure (HF) or myocardial infarction (MI) were included as the study population. Among them, 22 were in Referent (QRS duration <100 ms), 40 in Incomplete BBB (QRS duration 100 - 119), and 30 in Complete BBB (≥120 ms) groups. A pre-designed questioner was used for data collection. Properly written consent was taken from all the participants and this study was approved by the ethical committee of the mentioned university. All data were processed, analyzed, and disseminated by MS Office and SPSS version as per need. Results: In this study the QRS duration was observed to be linearly correlated with LV mass, LV diastolic dimension, septal wall thickness, posterior wall thickness and left atrial size (r=0.577, p< 0.001; r= 0.480, p< 0.001; r=0.583, p< 0.001; r=0.521, p<0.001 and r=0.418, p<0.001 res